Предмет: Математика,
автор: 495494Faya
a) 9(a - 12) =
b) 13 + 2(7 – x) =
c) 7u – 6(2 + C) =
d) 121 - (3 + y) 17 =
e) 25 + 2[12 - 3(x – 7)] =
f) [5 - 4(x - 9)] - 40 =
g) {[25x – 3(1 - y)] – z} =
h) {2[5t + 2(15 - 3c)] – k} + 3 =
i) [2x - (4 - y]) – z =
j) {21 – [5t - 205 - 3c)}] + 3 =
Ответы
Автор ответа:
0
Ответ:
а) 9а-108
b) 27-2x
c) 7u-12-6c
d) 70-17y
e) 35-6x
f) x-49
g) 22-22y-z
h) 375t-75ct+33-6c-k
I) 2x4-y-z
j) -181-5t-3c
Пошаговое объяснение:
кажется правильно
Похожие вопросы
Предмет: Русский язык,
автор: kalkutina02
Предмет: Английский язык,
автор: gaga337700
Предмет: Другие предметы,
автор: Айгерим2910
Предмет: Английский язык,
автор: vika88eroma